UTILIZING EXPERIMENTAL SIMULATION SOFTWARE TO ENHANCE STUDENT INVOLVEMENT IN CHEMISTRY PRACTICAL EXPERIMENTS (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
Technological advancements have created the potential to enhance teaching and learning across all levels of the education system. Computer simulation technologies have enhanced students' motivation, enthusiasm, and involvement in science instruction. The study investigated how ChemLab simulation software could impact students' involvement in secondary school chemistry laboratory experiments. Two hundred and nine senior secondary school students in science classrooms participated in the study. The result established a statistically significant effect of ChemLab simulation software on the respondent's intention to engage in chemistry lab experiments at F (1,207), 4.60 P< .05 with adjusted R2 indicating that ChemLab simulation software contributed about 9.11% of the variance in student's intention to engage in a chemistry lab experiment. The finding has implications for developing chemistry laboratory experiments in secondary schools.